Aptitude | Algebra | Question 5
Solve for x in the equation: log(2x – 1) + log(3) = log(x + 5)
x = -1/3
x = 1/3
x = 5/3
x = 8/5
Using the property of logarithms that states log(a) + log(b) = log(ab), we can simplify the equation as log(3(2x – 1)) = log(x + 5). Therefore, we have 6x – 3 = x + 5. Simplifying, we get 5x = 8, which gives us x = 8/5. Hence, the answer is D) x = 8/5.
Quiz of this Question
Please comment below if you find anything wrong in the above post
Whether you're preparing for your first job interview or aiming to upskill in this ever-evolving tech landscape, GeeksforGeeks Courses
are your key to success. We provide top-quality content at affordable prices, all geared towards accelerating your growth in a time-bound manner. Join the millions we've already empowered, and we're here to do the same for you. Don't miss out - check it out now!